Engaging High Water Users in Water Conservation #3: High Water Users’ Opportunities to Learn about Water Conservation - Pei-wen Huang; Alexa J. Lamm (EDIS)
Homeowners who use excessive amounts of water to irrigate their landscapes have specified demographic characteristics and have been identified as high water users. This 3-page fact sheet is the third in a series discussing how Extension can improve high water users' engagement in water conservation, focusing on how to effectively communicate with high water users about water conservation education. Written by Pei-wen Huang and Alexa J. Lamm, and published by the Department of Agricultural Education and Communication, August 2016.